VIRTUAL EDUCATION IN HIGHER EDUCATION INSTITUTIONS: CONTRIBUTION OF COLLABORATIVE LEARNING - Torres, Patricia Lupion; Marques Siqueira, Lilia María (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
This research has as central hypothesis a fact of Universities’ capacity and structure, even its disposal of both scientific and technological resources due this is a priviledge space for creation and experimentation of methodological proposals for distance education. This research aimed for presenting a collaborative learning as a methodology proposal as well with a changing role for students and teachers, when applied to virtual environments. In order to accomplish this project’s task, a previous bibliography research was run, this reviewed information on technological resources’ evolution, Brazilian and worldwide universities data, a formal study on EAD models already appyed and worked in Brazil, in cases as Vianney and Torres (2010), Rama (2009), Silvio (2000). A brief review on concepts of collaborative learning and its function on virtual university context. Accoring to Moran (2006), Torres (2004), Siqueira (2003) y Borba (2008), and interactivity concepts brought by Silva (2006). As a conclusion we suggest to use all pressumptions on collavorative learning, interactivity, learning Exchange and rol flexibility in communications and social relations in order to consider establishing a virtual pedagological University.